Implementasi Guided Inquiry-Blended Learning Melalui Teknik Flipped Classroom pada Mata Kuliah PAI untuk Meningkatkan Critical Thingking dan Penguatan Sikap Moderasi Beragama Mahasiswa - Ashoumi, Hilyah; Ahmad Akbar, Irwan (Journal of Islamic Education and Pedagogy, 2025)
This study focuses on the implementation of the Collaborative Inquiry Model based on the Flipped Classroom approach in the teaching of Islamic Religious Education (PAI) as an effort to strengthen students’ religious moderation in higher education. The purpose of this research is to examine the effectiveness of the model in enhancing students’ learning independence, critical thinking ability, collaboration skills, and internalization of religious moderation values, particularly regarding interreligious tolerance. The study employs a qualitative approach with a descriptive case study design conducted among students of the Faculty of Information Technology at KH. A. Wahab Hasbullah University, Jombang. Data were collected through participatory observation, in-depth interviews, and document analysis, and were analyzed using the interactive Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings reveal that the implementation of the Collaborative Inquiry Model based on the Flipped Classroom is effective in creating a reflective, participatory, and contextual learning process. In the first cycle, student engagement was still limited, with a learning readiness level of 65% and an average learning achievement of 74.5%. After strategic improvements were made in the second cycle, there was a significant increase: student readiness reached 87%, active participation rose to 85%, and the average learning achievement reached 86.8% with a 100% completion rate. Furthermore, collaborative activities among group members increased to 88%, indicating improved student cooperation and appreciation of diverse perspectives. The implementation of this model not only enhanced students’ cognitive aspects but also fostered moderate character and reflective attitudes in understanding religious values. The findings of this research contribute to the development of innovative and relevant strategies for religious education in the context of 21st-century learning, while also reinforcing the role of Islamic education in building an academic culture that is dialogical, inclusive, and grounded in the principle of Jaadilhum billati hiya ahsan.